The concept of controlling and its evolution (Buhalterinės apskaitos teorija ir praktika, 2014)
Due to an unstable financial-economic environment, a high level of competition and complex technological processes managers of enterprises are required to consider an opportunity of installing new innovative systems of enterprises activity organization and management. One of such systems is controlling, which is well known in foreign practice, but is seldom applied in Lithuania. The concept of controlling, its evolution, the structure of its elements, the problems of its installation in organizations have been widely reviewed in the works of German, Austrian, American, Russian authors. Despite the plenty of researches, there is no single opinion on economic conception, goals setting, tasks and functions of controlling. The polysemanticism, a variety of attitudes and conception's identification with other economic categories of the concept of controlling are a few many reasons that determined slow spread of this system in Lithuania. Attitudes of the authors who research the problems of controlling and their evolution are reviewed and summarized in the article, in order to give a clearer view of the contents of controlling conception.After reviewing the works of these authors, it has been determined that most of them review controlling in a systematic way, although they present it as an instrument, philosophy, a way of management etc. So first of all, controlling has to be analysed as a system. It was also determined that there is a close connection between controlling, internal control and management accounting; however the equalization of these definitions is impossible. After researching the development of the concept of controlling trends and attitudes it has been determined that in the evolution of the concept of controlling three main steps may be distinguished: controlling as a system of accounting; as an information system; as an instrument of enterprise's management. In every of these steps, different attitudes, formed by various authors, show up. Based on them, three main trends of the development of the concept of controlling were distinguished. The analysis of their evolution revealed that the location of controlling has been changing significantly during the last few decades. Yet, the least researched trend of controlling which still has no established attitudes is the one which was formed in the 21st century, The analysis has also revealed that the evolution of the concept's trends had influenced the contents of the conception of controlling, because every new attitude has appended the previous conception with new aspects.
Keywords: controlling; concept of controlling; evolution of concept of controlling